Extractive Spectrophotometric Determination of Silver(I) in Photo Films Waste Water - Krishna Reddy, B.; Subramanyam Sarma, L.; Jaya Kumar, C.; Varmada Reddy, A. (Asian Journal of Chemistry, 2010)
A sensitive and rapid spectrophotometric method has been developed for the determination of microgram amounts of silver(I) using benzildithiosemicarbazone (BDTSC) after extraction into chloroform. The influence of various foreign ions on the extraction of silver has also been studied. This method obeys Beer's law in the range of 0.3-5.5 μg/mL. The method has been successfully applied for the determination of silver in photo film waste water samples and the results are compared with atomic absorption spectrophotometric method.